Antimicrobial resistance in the meat industry and the impact of meat animal fecal microbiomes and resistomes on subsequent environments - Rice, Emily Ashton, author; Nair, Mahesh N., advisor; Belk, Keith E., committee member; Morley, Paul S., committee member; Noyes, Noelle N., committee member (Colorado State University. Libraries, 2022)
The discovery of antibiotics for human and animal use is considered one of the greatest medical advancements. However, the widespread use of antibiotics has caused concerns about a potential increase of antimicrobial resistance genes (ARGs) within microbial communities offering the opportunity for consumers to acquire antimicrobial resistant infections through the direct consumption of meat animals or through the environment via manure applications to crop land. Many consumers are becoming increasingly conscious of antibiotic usage labeling when purchasing meat products resulting in animal agriculture being considered a primary contributor for the dissemination of antimicrobial resistance (AMR). Although in recent years many advancements have been made to more fully understand the resistome of production animals preharvest and few post-harvest but, there are minimal studies that fully characterize the resistome of meat animals carcasses throughout the harvest process. Therefore, the purpose of the review (Chapter 2) is to outline opportunities to utilize metagenomic sequencing to pinpoint potential sources of antimicrobial resistance throughout meat processing. This could provide insight to better understand the potential sources of antibiotic resistant bacteria as a result of meat production. As bacteria can acquire ARGs through horizontal gene transfer or mutations, as an evolutionary advantage directly resulting from environmental pressures, the objective of the following study (Chapter 3) was to evaluate the relationships between the fecal resistome of different food animal species (avian, bovine, and porcine), the resistomes of meat from those animals, and resistomes of soil where feces was used as an amendment. Composite fecal samples (n = 20 per species) were collected from each commercial production facility and meat rinsate samples were (n = 20 per species) collected for each species at the time of harvest. After harvest, feces and litter were composted and applied as an amendment on agricultural land. After one growth season, soil samples (n = 20 per species) were collected separately for each species. Additionally, human waste solids were collected from wastewater treatment plants near each animal production operation (n = 14 per species), and soil samples amended with human waste solids were collected (n = 7 per species) from fields in close proximity to the broiler and bovine facilities. DNA was extracted, and the resistome library was prepped using the SureSelectXT reagent kit to prepare samples for target-enriched resistome sequencing targeting ARGs. Reads were analyzed using AMR++ v2 pipeline and sequences were aligned to the MEGARes v2 database to identify ARGs. Richness, evenness, and Shannon's diversity were calculated, and beta-diversity was analyzed using Bray-Curtis dissimilarity distances. Hierarchal clustering was performed using Ward's agglomeration in R. Regardless of species, fecal samples had a greater (P < 0.05) richness and evenness of ARGs compared to both meat and soil samples. For beta diversity, all the sampling types clustered (P < 0.05) individually (feces, meat, and soil) by species. Furthermore, within species each environment was dominated by different classes of ARGs indicating they have different resistomes. When resistance groups medically important for human health by the World Health organization were considered, human waste samples had a greater (P < 0.05) percentage (13%) of medically important resistance groups compared to all animal fecal samples (< 5%) (World Health Organization, 2017). The resistome of feces was richer and more diverse and clustered independently from both meat and soil indicating feces had a more unique resistome across the different species. This suggests that the fecal resistome may not influence meat and amended soil resistomes.
Keywords: bovine; porcine; avian; resistome; microbiome